Extended bound states in the continuum with symmetry-broken terahertz dielectric metasurfaces - Han, Song (2022)
Excitation of the non-radiative eigenmodes in photonics and metamaterials above their light cone, that is, the bound states in the continuum (BICs), has drawn fundamental and technological interest. However, the current studies on photonic BICs are mainly restricted to the characterization of the eigenmodes with fixed point group. Here, a fourfold rotationally symmetric (C4v) array of silicon resonators in a square lattice is investigated that reveals the traditional symmetry-protected (Γ-state) and accidental (off-Γ) BICs in the momentum space. Upon symmetry-breaking, BICs at Γ-state transform into quasi-states with decaying quality factors that obey the inverse-square law α−2 as a function of the structural asymmetry parameter α. Surprisingly, at larger asymmetries, multiple new states of extended BICs are observed beyond typical inverse-square law behavior. The structural asymmetry of a resonator provides an important degree of freedom for exploring the Friedrich–Wintgen and new accidental BICs that are topologically protected by robust polarization vortices. The extended family of sharp BIC resonances in all-dielectric silicon metasurfaces is extremely important for scalable applications in terahertz sensing, higher harmonic generation, and ultralow-power switching.